Type of CIDR but not eCG administration affected pregnancy per AI in Holstein heifers subjected to a 5-day estrus synchronization protocol - Albina Sanz; Mohanathas Gobikrushanth; Marcos G. Colazo (Journal of Applied Animal Research, 2022)
This study compared the effects of CIDR type and eCG treatment on ovarian follicular dynamics, estrus response and pregnancy per AI (P/AI) in Holstein heifers subjected to a 5-d estrus synchronization protocol. On Day 0, heifers (n = 133) received either a new or a once-used CIDR. On Day 5, CIDR was removed, 500 μg cloprostenol administered and heifers received or not 300 IU eCG (2 × 2 design). Heifers in estrus were inseminated 12 h after first observation. All heifers without estrus by 84 h after CIDR removal received 100 μg GnRH concurrently with AI. Ultrasonography was done in a subset of 77 heifers at CIDR insertion and removal, at AI and every 12 h after AI to determine follicular dynamics. Diameter of largest follicle at CIDR removal and AI was larger in heifers given a used CIDR (P < .05). The overall estrus response and ovulation (85.0 and 95.5%) did not differ between CIDR types, heifers given a new CIDR had greater P/AI (67.2 vs. 42.6%; P = .004). In summary, P/AI was reduced in dairy heifers treated with a used CIDR, despite having larger preovulatory follicles at AI. In addition, eCG treatment did not affect follicular dynamics, estrus response nor P/AI.